(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
This article aims to analyze the relationship between Natural Law and Labour Law, as well as to identify possible faults of the Brazilian labour legislation regarding the attention to natural law principles, while briefly discussing the history of labour protection and ideas for its making and improvement. All this will be done through the use of different sources that have had great relevance for the labour environment and for the study of jusnaturalism. Finally, an attempt will be made to present a solution for possible problems in the laws concerning labour in Brazil. The historical-bibliographical method will be used throughout the work.